Studying popular music culture - Wall, Tim (SAGE, 2013)
Popular music is an important part of our everyday life, entertaining, inspiring and even empowering us, but where did it come from, how is it made, what does it mean, and how does it eventually reach our ears? In this new edition, Tim Wall guides students through the many ways we can analyse music and the music industries, highlighting crucial skills and useful research tips.